A seqüência mafra superior \ Rio Do Sul inferior (Grupo itararé, permocarbonífero) em sondagens testemunhadas da região de mafra (SC), Margem Leste da Bacia do Paraná - Weinschütz, Luiz Carlos [UNESP]; Castro, Joel Carneiro de [UNESP] (My University, 2005)
The Permo-Carboniferous Harare Group crops out in the Matra area, represented by Campo do Tenente, Mafra and Rio do Sul formations; they correspond in subsurface to Lagoa Azul, Campo Mourão and Tacïba formations. A composite sampling of the Group was performed through drilling of six wells, which average 60 m in depth; three of them cored the depositional sequence here designated as Upper Mafra\Lower Rio do Sul. The Upper Mafra Formation were sampled by TC-4 and BR-5 wells, and it consists of three units: the lower two are sandy, glacial-deltaic and fluvial-deltaic in origin, corresponding to a lowstand tract. The last unit is composed of two dirtying-upward successions of sandstone, diamictite and rhythmite, interpreted as deglaciation/transgressive events, and well represented in BR-5 drilling. The Lower-Rio do Sul Formation (Lontras Shale) is formed by two marine units: the lower one is represented by shale and bioturbated siltstone which culminate the previous deglaciation, transgressive succession, while the upper one, sampled by SL-2 well, is formed by shale and thin, turbidite sandstone, attributed to a highstand tract.

O Grupo Itararé (Permocarbonífero) aflora na região de Mafra (SC), onde é representado pelas formações Campo do Tenente, Mafra e Rio do Sul; em cada uma destas duas últimas unidades foram reconhecidos três intervalos cronoestratigráficos, designados Mafra inferior, médio e superior, e Rio do Sul inferior, médio e superior. Tais unidades correspondem, em subsuperfície, aos ciclos/formações Lagoa Azul, Campo Mourão e Taciba. Uma amostragem composta do grupo foi obtida por seis sondagens testemunhadas, que alcançaram em média 60 m de profundidade; três dessas sondagens amostraram a seqüência deposicional designada Mafra superior/ Rio do Sul inferior, e que é objeto do presente trabalho. A Formação Mafra superior, investigada pelos poços TC-4 e BR-5, compreende duas unidades deposicionais, de origem deltaica-glacial e fluvial-deltaica, correspondendo a um trato de mar baixo; sucedem outras duas unidades, com argilosidade crescente, formadas por arenito, diamictito e ritmito, representando eventos de deglaciação de um trato transgressivo. A Formação Rio do Sul inferior compreende duas unidades, uma de folhelho fossilífero e siltito bioturbado, e a segunda de folhelho e arenito síltico (turbidito), sendo esta testemunhada no poço SL-2; tais unidades marinhas constituem, respectivamente, a culminância transgressiva do processo de deglaciação e o trato de mar alto.
The upper mafra\lower Rio do sul sequence Ilararé Group, Permo-Carboniferous from composite sampling by drilling in the Mafra region (State of Santa Catarina), eastern border of the Paraná Basin
Keywords: Glacial sedimentation; Itararé Group; Paraná Basin; Permo-Carboniferous; Sequence stratigraphy; composite; deltaic deposit; depositional sequence; diamictite; drilling; glaciofluvial deposit; rhythmite; sampling; sandstone; sequence stratigraphy; Brazil; Mafra; Santa Catarina; South America